Financial Benefits of Private Clouds for the Local Government Units - Szałkowska-Strzelecka, Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The main objective of this paper is to discuss financial benefits of a private cloud for the local government. A traditional approach in financial analysis of using IT in the public sector is analysed. At first, the article describes some methods used to assess the benefits of using IT in the context of the existing literature. Then considerations are presented concerning investment processes of IT in the units of local government. The issues related to nature of co-financing of IT projects from European Funds are discussed. In addition, legal and organisational requirements for this are indicated. In the following part we present the local administration’s perception of financial advantages of cloud computing. These considerations are supported by the material derived from interviews conducted in several local government units. The summary contains conclusions and talks about the need for developing a method that would allow to analyse the financial benefits for the local administration generated by a private cloud.